The effects of cigarette smoking behavior and psychosis history on general and social cognition in bipolar disorder. (21st September 2016) - Ospina, Luz H; Russo, Manuela; Nitzburg, George M; Cuesta‐Diaz, Armando; Shanahan, Megan; Perez‐Rodriguez, Mercedes M; Mcgrath, Meaghan; Levine, Hannah; Mulaimovic, Sandra; Burdick, Katherine E
Abstract : Objectives: Several studies have documented the prevalence and effects of cigarette smoking on cognition in psychotic disorders; fewer have focused on bipolar disorder (BD). Cognitive and social dysfunction are common in BD, and the severity of these deficits may be related both to illness features (e.g., current symptoms, psychosis history) and health‐related behaviors (e.g., smoking, alcohol use). The current study assessed the influence of cigarette smoking on general and social cognition in a BD cohort, accounting for illness features with a focus on psychosis history. Methods: We assessed smoking status in 105 euthymic patients with BD, who completed a comprehensive battery including social (facial affect recognition, emotional problem‐solving, and theory of mind) and general (the MATRICS Consensus Cognitive Battery and executive functioning) cognitive measures. We compared smokers vs nonsmokers on cognitive performance and tested for the effects of psychosis history, premorbid intellectual functioning, substance use, and current affective symptoms. Results: Within the nonpsychotic subgroup with BD (n=45), smokers generally outperformed nonsmokers; by contrast, for subjects with BD with a history of psychosis (n=41), nonsmokers outperformed smokers. This pattern was noted more globally using a general composite cognitive score and on social/affective measures assessing patients' ability to identify emotions of facial stimuli and solve emotional problems. Conclusions: Cigarette smoking differentially affects performance on both general and social cognition in patients with BD as a function of psychosis history. These results suggest that there may be at least partially divergent underlying neurobiological causes for cognitive dysfunction in patients with BD with and without psychosis.